Font Size: Small Medium Large Career Perception at the Republic Indonesian Police Organization Impact of Distributive Fairness, Procedural Fairness and Career Satisfaction on Affective Commitment - Tjahjono, Heru Kurnianto; Palupi, Majang; Dirgahayu, Paramitasari (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
In general, this study describes the phenomenon of career's fairness and the importance of career for the satisfaction and commitment of members of the police in organization. This test also explains whether a career in human resource management practices explain the higher level of commitment, namely affective commitment. Specifically, first to conduct further testing of the impact of career distributive and career procedural fairness on career satisfaction and affective commitment. The second was to test the impact of career satisfaction on the affective commitment. The third was to describe the condition of career fairness, career satisfaction and affective commitment at the police resort organization in province X. The data analysis technique used in this study is SEM which is operated through the AMOS software program. The population of this research was 134 officers of police resort organization. The results indicated that career distributive and procedural fairness are strong predictor to explain career satisfaction. Then both of career fairness type and career satisfaction are predictor to explain affective commitment.